Decentralization puzzles a political economy analysis of irrigation reform in the Philippines - Araral, Eduardo K. Jr (ProQuest, UMI Dissertations Publishing, 2006)
In the 1970's, the Philippines embarked on a program to decentralize the management of public irrigation. Early studies have shown that these reforms led to consistently positive results and earned widespread international documentation and recognition as a role model. Twenty years later, however, an examination of the program now indicates problems of poor performance.